Analisis Struktur Narasi dalam Cerita Rakyat Nusantara : Studi pada Cerita Malin Kundang - Aprilia Vavalin; Firza Afrian Wardana; Rani Putri Khanza (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This research aims to analyze the narrative structure in Indonesian folklore with a focus on the story "Malin Kundang". The research uses a descriptive qualitative approach to explore narrative elements such as plot, characters, setting, themes and moral messages. Data was obtained through literature study from various folklore sources that tell the story of "Malin Kundang". The research results show that this story has a chronological narrative structure, starting from introduction, conflict escalation, climax, to resolution. The theme of this story is a child's disobedience towards his mother, which ends with a deep moral message. This research emphasizes the importance of Indonesian folklore as a medium for conveying moral values ​​in society. The research results show that the story "Malin Kundang" has a clear narrative structure, with a chronologically structured plot, starting with the introduction of the characters and background, followed by conflict escalation, the climax of the story, and a moral message at the end of the story. The theme of this story is a child's disobedience to his mother and the consequences. In short, the narrative structure of the story "Malin Kundang" conveys deep moral values ​​and is entertaining. This study also shows that the structure of Indonesian folklore often contains strong moral messages.